Presence of Anthropogenic Markers in Water: A Case Study of the Guaporé River Watershed, Brazil. Issue 3 (1st February 2018) - Camotti Bastos, Marilia; Rheinheimer dos Santos, Danilo; Monteiro de Castro Lima, José A.; le Guet, Thibaut; Santanna dos Santos, Maria A.; Zanella, Renato; Aubertheau, Elodie; Mondamert, Leslie; Caner, Laurent; Labanowski, Jérôme
Abstract : Southern Brazil is an agricultural region that is experiencing strong growth in both cereal and animal production. The intensification of agricultural practices, as well as the growing urbanization in this region, also generates strong anthropogenic pressures on the aquatic environment. In Brazil, the lack of sewage treatment and the wide use of waste (liquid or solid) for the fertilization of soils are likely to favor the spread of pharmaceuticals in the surrounding environment. Considering the benefits of the determination of anthropogenic markers in the environment, the study aimed to monitor the presence of carbamazepine (CBZ) and sucralose (SCR) in the Guaporé River, representative of a southern Brazilian rural watershed. Both carbamazepine and sucralose are measured in water by polar organic chemical integrative samplers (POCIS) (CBZ: lower than limit of detection (< LOD) to 746 μg g −1 and SCR: <LOD) and in the river biofilms (CBZ: <LOD to 3.6 ng g −1 and SCR: <LOD to 139.3 ng g −1 ) to give an overview of the level of aquatic contamination. The use of sucralose and carbamazepine as tracers of anthropogenic activity proved promising, as was the use of biofilms and POCIS as samplers. Biofilm and POCIS are two complementary techniques. Biofilms are able to identify contaminated environment sites by the capture of SCR as a human marker and POCIS are capable to capture the CBZ compounds with higher efficiency in polluted sites than biofilms. Abstract : Sucralose and carbamazepine are promising tracers of anthropogenic activity. Their monitoring in the environment could be useful to estimate the impact of human activities. Integrative passive samplers, POCIS, and epilithic biofilms are used to evaluate the impregnation of aquatic environment by these compounds in Brazil. Cities are the main contributors of environmental pollution and both sampling techniques proved to be complementary.